"Gateway to Hell": A Nazi Mass Grave, Forensic Scientists, and an Australian War Crimes Trial. (22nd November 2018) - O'Donnell, Peggy
Abstract: In June 1990 a team of Australian forensic scientists arrived in Soviet Ukraine to exhume a half-century-old grave of Jewish Holocaust victims. Some three thousand miles away in Adelaide, Australia a committal hearing was about to determine whether a Ukrainian-born but naturalized Australian citizen named Ivan Polyukhovich would stand trial for their murders. This article tells the story of how the forensic scientists ended up in Serniki and what they found. It considers the importance of this exhumation both for the past—as an episode of the Holocaust—and for the future use of forensic science in reconstructing acts of mass killing.